CD11c+ dendritic cells mediate antigen‐specific suppression in extracorporeal photopheresis. (8th November 2020) - Hackstein, H.; Kalina, A.; Dorn, B.; Keil, I. S.; Baal, N.; Michel, G.; Brendel, C.; Neubauer, A.; Jakob, T.; Bein, G.
Summary: Extracorporeal photopheresis (ECP) represents one of the most widespread and effective cell therapies for graft‐ versus ‐host disease and other T cell‐mediated disorders. However, the key factors affecting the therapeutic efficacy of ECP remain unclear. We hypothesized that therapeutic effects are mediated by ECP‐treated antigen‐presenting dendritic cells (DC). To test this hypothesis, we used the experimental model of contact hypersensitivity (CHS). The ECP's therapeutic activity improved when the total cell dose of the ECP‐treated cells was increased. We used different haptens during sensitization to demonstrate that the anti‐inflammatory activity of ECP is antigen‐specific. This confirmed the hypothesis that professional antigen‐presenting cells are involved in the mode of action. Also, the ECP's therapeutic activity was abrogated by the depletion of CD11c + DC, which represents fewer than 1% of all the ECP‐exposed cells. Finally, we confirm the critical importance of CD11c + DC for ECP activity by showing that only a few purified CD11c + DC are sufficient to mediate its therapeutic effect. The finding that ECP‐treated, physiological antigen‐presenting DC alone mediate antigen‐specific modulation of a pathological immune response may result in better‐targeted interventions when treating patients. Abstract : The mechanism of action of extracorporeal photopheresis (ECP) is largely unknown. Here, we demonstrate, using a preclinical in vivo model, that the antigen‐specific immunosuppressive effect of ECP is mediated solely by CD11c + dendritic cells.